Analysis of the Pattallassang Village Financial System Against Village Community Empowerment During the Pandemic (Covid-19). - nasrullah nasrullah; Kahar Kahar; Haslindah Haslindah; Moh. Aris Pasigai; Nur Wahida Basri; Sultan Sarda (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the financial system of Pattallassang village for empowering rural communities during the pandemic (covid-19). The financial system in empowering rural communities can be seen from an activity that prepares and determines a goal to be achieved. The type of research used is qualitative research. Data were collected by observation, interview, and documentation methods. In this study, the data source used was primary data collection. The results of this study indicate that the village financial system on empowering rural communities during the pandemic (covid-19) has a positive effect on rural communities because it is very helpful for rural communities from an economic perspective